Modifikasi Strategi Pembelajaran Langsung dengan Demonstrasi untuk Meningkatkan Koginitif Siswa - Hayati Arifah Al-Bahri; Nurul Hafidzah; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the application of a modified direct learning strategy combined with the demonstration method to improve students' cognitive abilities. The direct learning strategy is an approach that emphasizes the systematic and gradual delivery of material, so that students can understand concepts in a more structured manner. However, in practice, this strategy needs to be modified to be more engaging and appropriate to the characteristics of students. The demonstration method is used as a form of reinforcement in the learning process, where students not only receive information verbally but also directly observe the processes, events, or concepts being studied. This allows students to gain a more concrete and meaningful learning experience. Modifications to the learning strategy are carried out through adjustments to models, methods, media, and learning facilities and infrastructure to optimally support the achievement of learning objectives. Students' cognitive abilities are the main focus of this study, which include aspects of knowledge, understanding, application, analysis, evaluation, and creation according to Bloom's taxonomy. With the implementation of appropriate learning strategies, students are expected to be able to develop more active and critical thinking skills. The results of the study indicate that a modified direct learning strategy with the demonstration method has the potential to significantly improve students' cognitive abilities. Therefore, this approach can be used as an alternative, effective learning strategy to create a more interactive, engaging, and meaningful learning process.